Fostering Environmental Awareness Character in Elementary Education Through the Economic Green Living Approach - Retno, Raras Setyo; Yuhanna, Wachidatul Linda; Utami, Sri (Indonesian Values and Character Education Journal, 2024)
The global issue of environmental degradation necessitates education that fosters environmental awareness among students from an early age. Green living is an effective learning approach to cultivate students' environmental concern while simultaneously developing their independence. This study aims to analyze the development of environmental awareness among elementary school students through the economic green living approach, which applies the 5R principles: refuse, reuse, recycle, reduce, and replant. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The collected data were analyzed using the interactive model by Miles and Huberman, which involves data reduction, data presentation, and continuous conclusion drawing. The results reveal that the implementation of the 5R principles among students includes activities such as waste recycling, greening, reusing discarded items, waste reduction, and rejecting plastic bags. The process cultivates characteristics such as independence, responsibility, discipline, creativity, and collaborative skills. This study concludes that the economic green living approach, utilizing the 5R principles, is effective in shaping students’ environmental awareness while equipping them with life skills relevant to addressing environmental sustainability challenges.